Estrategias de intervención psicopedagógica en el desarrollo de habilidades socioemocionales en niños con trastornos del espectro autista (TEA) - Nuñez Fuentes, Cinthya Leonela (2025)
Education in the early years of life is an essential pillar for the comprehensive development of human beings. In this regard, acquiring and strengthening social-emotional skills becomes a key component, especially in children with Autism Spectrum Disorder (ASD). The purpose of this research is to determine the strategies teachers use to develop the skills of children with ASD. Additionally, identify the factors contributing to the development of children with this condition in terms of social-emotional skills, with the goal of developing a guide to psychoeducational intervention strategies for managing social-emotional skills in children with ASD. That is why this research adopted a qualitative approach, using two instruments: a survey and an observation from applied to diagnosed students and teachers at the American high School Educational Unit in the Riobamba canton, Chimborazo province, the findings of the research are duly related to determning teachers’ strategies according to the development of social-emocional skills, they also agree with the factors involved in the development of children with this disorder in relation to their social-emotional skills, finally, the research paper proposes a guide to psychopedagogical strategies, for the social-emotional development of children with ASD, which are expected to serve as educational support within the educational institution.